The Influence of Green Financing and Return Dynamics on Environmental, Social, and Governance Performance: Evidence from Indonesia’s Islamic Banking Sector - Iskandar; Rauzatul Jannah; Burhan Uluyol; Hussein 'Azeemi Abdullah Thaidi; Siti Najma (Department of Sharia Economic Law, Faculty Sharia and Law, UIN Sunan Gunung Djati Bandung, 2026)
This study aimed to examine the influence of green financing and return dynamics on ESG performance in Indonesia’s Islamic banking sector. The issue was important considering the growing role of Islamic banks in promoting sustainable finance and strengthening institutional resilience within dynamic financial markets. A quantitative method was adopted based on secondary weekly data from six Islamic banks in Indonesia during 2020–2025 (1,878 observations). ESG score was the dependent variable, while green financing and weekly return were independent variables. The analysis applied GARCH model to estimate the association between the variables and to capture volatility persistence over time. The results showed that green financing had a positive and statistically significant effect on ESG performance. Islamic banks that consistently allocated funds to green financing tended to achieve higher and more stable ESG scores. In contrast, short-term return fluctuations did not significantly affect ESG performance, suggesting that sustainability practices were driven more by long-term strategic commitments than by temporary market dynamics. GARCH estimation confirmed the persistence of ESG volatility over time. The results showed that green financing served as a key driver of sustainability performance in Islamic banking and supported long-term institutional stability. Important insights were provided for bank management and regulators to strengthen the integration of sustainable financing strategies in line with Islamic finance principles.